Influence of R wave analysis upon diagnostic accuracy of exercise testing in women. Issue 2 (August 1982) - Ilsley, C; Canepa-Anson, R; Westgate, C; Webb, S; Rickards, A; Poole-Wilson, P
Abstract : Exercise electrocardiography in women with chest pain is associated with a high incidence of false positive ST segment depression. The recent observation that changes in R wave amplitude during exercise can also be used diagnostically may improve the value of stress testing in women. The results of 12 lead treadmill exercise and coronary angiography were reviewed in 62 women, mean age 51 years, presenting with "angina" without previous myocardial infarction. These were compared with exercise results in 14 healthy asymptomatic volunteers with a mean age of 26 years. In addition to conventional ST analysis, R wave amplitude changes during exercise, measured in leads II, III, a VF, and V4 to 6, were examined. While the sensitivity and specificity of ST and R wave changes were similar at about 67%, their combined interpretation was helpful. If both ST and R wave criteria were negative the predictive accuracy for normal coronary angiography was 94% (17/18). Alternatively, in tests showing both ST depression and an abnormal R wave response, coronary angiography was always abnormal (13/13). None of the normal volunteers developed ST segment depression and 93% (13/14) had a normal R wave response. If both were positive, however, coronary angiography was always abnormal (13/13). Although stress test interpretation in women is difficult, R wave analysis is a useful adjunct to ST change and can improve the predictive accuracy of the test in a significant number of patients.